UMA NOVA ESPÃ‰CIE DE ð˜Šð˜¦ð˜³ð˜£ð˜¦ð˜³ð˜°ð˜¥ð˜°ð˜¯ DO BRASIL (TETTIGONIIDAE, LYSTROCELLINAE) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2020)
UMA NOVA ESPÃ‰CIE DE ð˜Šð˜¦ð˜³ð˜£ð˜¦ð˜³ð˜°ð˜¥ð˜°ð˜¯ DO BRASIL (TETTIGONIIDAE, LYSTROCELLINAE)